Development Strategy of Halal Industry Ecosystem in North Sumatra - Ichsan, Reza Nurul (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This study aims to highlight the importance of meeting the needs of Halal certification significantly affects the innovative performance of halal certified food companies, which leads to improved market performance. Thus, the problem formulation of this research is how the Halal Industry Ecosystem Development Strategy in North Sumatra. The research method used in this study is Qualitative methods such as interviews with industry experts and stakeholders will provide valuable insights into the condition of the Halal industry in North Sumatra. The results of this study found that the halal industry in North Sumatra shows great potential for growth and development, with promising opportunities for expansion. Collaboration between government agencies, industry associations, businesses and consumers will be crucial in driving innovation and creating a thriving ecosystem for Halal products and services. By working together to achieve common goals, we can ensure the continued growth and prosperity of the Halal industry in North Sumatra in the years to come.